The Role of NGOs in Environmental Policy Failures in a Developing Country: The Mismanagement of Jamaica's Coral Reefs. (1st February 2003) - Haley, Michael; Clayton, Anthony
Recent years have seen a proliferation of non-governmental organisations (NGOs) with a mission to help redress various social and environmental problems, but the effectiveness of these organisations in carrying out their stated goals is rarely assessed or critically examined. It has become increasingly clear, however, that these organisations vary greatly in their level of competence and professionalism. Many of them are ineffective, and in some cases they may even exacerbate the problems they set out to solve. These difficulties are based upon flawed assumptions about how civil society can correct social ills, and about how institutions that are intermediate between the individual and the state can carry out effective change. To illustrate these points with an environmental example, we present the case of Jamaica's coral reefs, which have been under stress for decades. Both the causes of reef degradation and the solutions to these problems can be clearly outlined. Many well-intentioned organisations and individuals have been involved in the attempt to stem or reverse the damage, and significant funding has been channelled through these agencies. In spite of this, there has been no documented improvement in the condition of the reefs, apart from some natural regeneration that owed nothing whatever to any human activity. The problem is that the known solutions have not been implemented. This has happened for several reasons. First, government organisations have actively encouraged NGOs to undertake the responsibility of protecting sections of the coastline, but without any proper assessment of the capacity of those organisations to do so, and in some cases actively preventing them from acquiring that capacity. Second, the proliferation of NGOs (in part a response to the availability of funding) has been counter-effective, resulting in duplication of effort, competition for limited funds, and conscious or unconscious misrepresentation of results. Third, the utilisation of NGOs to solve environmental problems often results in an increase in the number of levels of management, resulting in inefficient utilisation of funds. The known solutions to the degradation in the Jamaican marine environment principally involve (a) reducing fishing pressures at a national level and (b) the reduction of pollution by local municipalities. The effective role of NGOs in bringing about these two solutions therefore differs: where national changes are necessary, government centralisation and effective enforcement are necessary, although NGOs could still play a useful auxiliary or augmenting role. With local problems like municipal pollution, NGOs may be better able to lead in catalysing and implementing change, although the government could usefully provide co-ordination and support. These differences illustrate the fallacy in the simplistic assumption that rising public concern, increased levels of funding and a growing number of people and/or organisations involved in conservation will lead to environmental improvement. Effective hierarchical organisation is still a prerequisite for bringing about effective solutions, although the mode of organisation adopted should be a function of the particular solution necessary. Finally, since many NGOs have effectively functioned as parasitical organisations that have consumed public funding without any discernible public benefit, NGOs should be subject to the same scrutiny and assessment as any private sector organisation contracted to the government and/or donor agencies, and those who fail to perform should be barred from further receipt of public funds.